2008
DOI: 10.2147/opth.s2774
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional regulation of ocular blood flow: A risk factor for glaucoma?

Abstract: Primary open angle glaucoma (OAG) is a multifactorial optic neuropathy characterized by progressive retinal ganglion cell death and associated visual fi eld loss. OAG is an emerging disease with increasing costs and negative outcomes, yet its fundamental pathophysiology remains largely undetermined. A major treatable risk factor for glaucoma is elevated intraocular pressure (IOP). Despite the medical lowering of IOP, however, some glaucoma patients continue to experience disease progression and subsequent irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 128 publications
2
37
0
Order By: Relevance
“…Glaucomatous optic nerve damage has recently been suggested to be the result of vascular and other pathogenic mechanisms in addition to elevated intraocular pressure [28,29]. The dysregulation of optic nerve circulation found in OSAHS may cause RNFL changes that are similar to glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucomatous optic nerve damage has recently been suggested to be the result of vascular and other pathogenic mechanisms in addition to elevated intraocular pressure [28,29]. The dysregulation of optic nerve circulation found in OSAHS may cause RNFL changes that are similar to glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Whether abnormal ONH blood flow response patterns to changes in OPP predispose to ocular vascular diseases is unknown. For several common eye diseases such as diabetic retinopathy[ 2 , 35 ] and glaucoma[ 5 , 6 , 36 ] abnormalities in ocular blood flow autoregulation have been reported. In primary open glaucoma reduced OPP is a risk factor for the disease[ 6 , 37 39 ] and it has been hypothesized that ONH blood flow falls below the lower limit of autoregulation during periods of low blood pressure or high IOP[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both impaired blood flow and impaired vascular autoregulation have been described in glaucoma patients (Flammer et al, 2002 ; Feke and Pasquale, 2008 ; Moore et al, 2008 ; Feke et al, 2011 ). Large epidemiologic studies have found adverse associations between POAG and low ocular perfusion pressure (OPP) (Hulsman et al, 2007 ; Leske, 2009 ) or low systemic blood pressure (Bonomi et al, 2000 ).…”
Section: Glaucoma and Vascular Dysfunctionmentioning
confidence: 99%